Determining Optimal Follow-up for Patients With Anal Cancer Following Chemoradiation. (May 2020) - Frazer, Marissa L.; Yang, George; Felder, Seth; McDonald, Jordan; Sanchez, Julian; Dessureault, Sophie; Imanirad, Iman; Carballido, Estrella; Kim, Richard D.; Hoffe, Sarah E.; Frakes, Jessica M.
Abstract : Background: US health care is increasingly defined by over expenditure and inefficiency. Optimizing patient follow-up is critical, especially in cancers treated with high control rates. To optimize patient care, this study assessed time to disease recurrence or toxicity in patients with anal carcinoma. Materials and Methods: In total, 140 patients with biopsy-proven, nonmetastatic anal carcinoma, treated with chemoradiation utilizing intensity-modulated radiation therapy, were identified from our institutional database. This retrospective study evaluated local recurrence (LR), distant metastasis (DM), overall survival (OS), and late ≥grade 3 toxicity (LG3T). Patients were followed posttreatment every 3 months for 2 years, every 6 months in years 3 to 5, then yearly thereafter per NCCN recommendations. Results: The median age and follow-up was 58 years and 27 months, respectively. Patients were categorized into high (n=61; 44%) and low (n=77; 55%) risk groups based on stage. The 2-year LC, DMFS, and OS were 93%, 94%, and 89% and 5-year LC, DMFS, OS were 92%, 87%, and 85%, respectively. Overall, there were 29 events (9 LR, 11 DM, and 9 LG3T), with 62% of events occurring within year 1 and 79% within 2 years. Stratified by event type, at 2 years 89% of LR, 64% of DM, and 89% LG3T were identified. At the remaining follow-up points, the event incidence rate was 1.3%. Conclusion: With the majority of recurrences/toxicities occurring within the first 2 years, a reduction in follow-up during years 3 to 5 may provide adequate surveillance. Revisions of the current recommendations could maximize resources while improving patient quality of life.